Effects of the Laschamps Excursion on Geomagnetic Cutoff Rigidities - Jiawei Gao; Monika Korte; Sanja Panovska; Zhaojin Rong; Yong Wei (Geochemistry, Geophysics, Geosystems, 2022)
Abstract Today's geomagnetic field can prevent energetic particles, including solar energetic particles and galactic cosmic rays, from directly hitting the Earth's atmosphere. However, when the geomagnetic field strength is significantly decreased during geomagnetic field excursions or reversals, the geomagnetic field shielding effect becomes less prominent. Geomagnetic cutoff rigidity, as a quantitative estimation of the shielding effect, can be calculated using trajectory tracing or theoretical equations. We use a recent high‐resolution continuous geomagnetic field model (LSMOD.2) to study the geomagnetic cutoff rigidity during the Laschamps excursion. Global grids of the geomagnetic cutoff rigidities are presented, in particular for the excursion midpoint when the geomagnetic field is weak and not dipole‐dominated anymore at Earth's surface. We compare the cutoff rigidity calculation results between a trajectory tracing program and theoretical equations and we find that the influence of the non‐dipole component of the geomagnetic field cannot be ignored during the excursion. Our results indicate that the exposure of Earth's atmosphere to energetic particles of cosmic and solar origin is high and nearly independent of latitude in the middle of the Laschamps excursion. Our results will be useful for future studies associated with cosmic radiation dose rate and cosmogenic isotope production rate during the Laschamps excursion.